Sistem Pendidikan Pesantren Salafiyah Syafi’iyah Sorong - Yudiawan, Agus (Al-Fikr: Jurnal Pendidikan Islam, 2017)
Salafiyah Syafi'iyah Islamic Boarding School is a combination of Religion and general science. This Islamic boarding school still maintains its traditional system by using the method of sorogan and wetonan in carrying out the process of its education system especially in the study of classical books while the quality of education in the Salafiyah Syafi'iyah Islamic Boarding School is quite good. Educational programs in the Salafiyah Syafi'iyah Islamic Boarding School, namely formal education programs including Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs), non-formal education in the form of diniyah education for 6 years for SD/MI graduates and 3-year program for graduates MTs. The social program includes preaching and social activities of students. One of the factors supporting the implementation of the education system in the Salafiyah Syafi'iyah Islamic Boarding School which is urgent and important is the building. From year to year, Salafiyah Syafi'iyah Islamic Boarding School experienced a development starting with buying land or land until now it has become a building that can be occupied and to study Islam. The inhibiting factor in the implementation of the Salafiyah Syafi'iyah Islamic Boarding School is the most urgent matter in terms of dormitory because, with the increasing number of students, a large place for students to live or live is needed.